Thinking Things: Images of Thought and Thoughtful Images - Larsson, Dr Chari (Transformations, 2016)
French art historian Georges Didi-Huberman has enigmatically declared that “Montage is the art of producing this form that thinks.” What does it mean for an image to think? The fundamental principles of montage, such as juxtaposition and shock are well known. Perhaps, however, there is another way to speak of montage, when it is deployed as a mode of knowledge. By claiming that images are capable of thinking, this essay argues that Didi-Huberman is taking up Gilles Deleuze’s proposal that cinema does not merely imitate or reflect philosophy, but produces its own philosophical project. For Deleuze, the challenge facing philosophy was to overcome the assumptions concerning what thinking is, a return to a ground zero of what representation can possibly be. Didi-Huberman’s arguments signal an alternative way of treating images beyond what Deleuze calls “representation,” or thought based on resemblance, recognition and identity. To do this, Didi-Huberman retrieves montage from the historical avant-garde and explores its epistemological potential. By emphasising montage’s capacity to create new meaning and generate new lines of thought, images become theoretical objects, things that “think.”